2021
DOI: 10.1021/acs.nanolett.1c00608
|View full text |Cite
|
Sign up to set email alerts
|

Healable Lithium Alloy Anode with Ultrahigh Capacity

Abstract: Effective recycling of spent Li metal anodes is an urgent need for energy/resource conservation and environmental protection, making Li metal batteries more affordable and sustainable. For the first time, we explore a unique sustainable healable lithium alloy anode inspired by the intrinsic healing ability of liquid metal. This lithium alloy anode can transform back to the liquid state through Li-completed extraction, and then the structure degradation generated during operation could be healed. Therefore, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…In this regard, constructing a substrate with uniformly distributed nanoseeds as “sodiophilic sites” is beneficial to decrease the overpotential and enable a uniform deposition of Na metal. To date, a series of metallic materials (e.g., Sn, Sb) have been proven that they can reduce the nucleation barrier of Na due to the alloy-type reaction during the electrochemical process . However, the great volume variation of the alloy-type anodes upon ion insertion/extraction usually causes electrode pulverization and then fast capacity decay .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, constructing a substrate with uniformly distributed nanoseeds as “sodiophilic sites” is beneficial to decrease the overpotential and enable a uniform deposition of Na metal. To date, a series of metallic materials (e.g., Sn, Sb) have been proven that they can reduce the nucleation barrier of Na due to the alloy-type reaction during the electrochemical process . However, the great volume variation of the alloy-type anodes upon ion insertion/extraction usually causes electrode pulverization and then fast capacity decay .…”
Section: Introductionmentioning
confidence: 99%
“…To date, a series of metallic materials (e.g., Sn, Sb) have been proven that they can reduce the nucleation barrier of Na due to the alloy-type reaction during the electrochemical process. 24 However, the great volume variation of the alloy-type anodes upon ion insertion/extraction usually causes electrode pulverization and then fast capacity decay. 25 In this regard, Li and co-workers demonstrated that Sn@C can serve as an ideal substrate for Na deposition, 26 27 Nevertheless, the synthesis of the above unique structures generally requires time-consuming and tedious synthetic procedures, thus limiting their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with liquid electrolytes, solid polymer electrolytes (SPEs) have attracted wide attention due to their high safety and superior processability [1–6] . In particular, the good mechanical properties of SPE can effectively restrain the growth of lithium dendrite, as a consequence, SPEs can utilize lithium‐metal cathode to achieve high energy densities [7–10] . To obtain SPEs with high ionic conductivity, polymers with high dielectric constant and lithium salt solvation ability, such as Poly(ethylene oxide) (PEO) and Polyacrylonitrile (PAN) are widely used [11] .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In particular, the good mechanical properties of SPE can effectively restrain the growth of lithium dendrite, as a consequence, SPEs can utilize lithiummetal cathode to achieve high energy densities. [7][8][9][10] To obtain SPEs with high ionic conductivity, polymers with high dielectric constant and lithium salt solvation ability, such as Poly(ethylene oxide) (PEO) and Polyacrylonitrile (PAN) are widely used. [11] Among them, PEO is the most studied owing to its flexible ether oxygen bond that can effectively dissolve lithium salt through the solvation effect.…”
Section: Introductionmentioning
confidence: 99%
“…With the large-scale popularization of lithium-ion batteries, lithium resources become increasingly expensive, and thus the recycling of lithium attracts more and more attention. , When the free electrons in the Li-Naph/DME solution are consumed, the Li-Naph complex will lose its reduction activity and be oxidized to free Li + and naphthalene. To improve lithium resource utilization, we further design an accessible approach to retracting Li + from the inactive Li-Naph/DME waste solution, as illustrated in Figure a.…”
mentioning
confidence: 99%